Abscesstonsillectomy: Uni- or bilateral? - Fauck, Vanessa; Schinz, Katharina; Alexiou, Christoph; Mantsopoulos, Konstantinos; Iro, Heinrich; Müller, Sarina Katrin (Laryngo-Rhino-Otologie, 2022)
Objective In addition to an empirical use of antibiotics for treatment of a peritonsillar abscess (PTA) there is a drainage of pus or the abscess tonsillectomy. Postoperative bleeding after abscesstonsillectomy (ABTE) is this surgery's most feared complication which can rarely lead to patients' deaths. The objective of this study was to compare bleeding complications of ABTE with and without contralateral tonsillectomy (TE) and to analyze the occurrence of a metachronous PTA at the contralateral side. Methods Retrospective study of n= 655 patients undergoing ABTE with and without TE of the contralateral side from January 2004 to February 2019. Bleeding complications needing surgical hemostasis were analyzed regarding demographic and surgical parameters. In addition, occurrence of PTA and need for ABTE of the contralateral side after unilateral ABTE were evaluated. Results Overall, 10/655 (1.5 %) patients presented with postoperative bleeding after ABTE. In 404/655 an ABTE with contralateral TE was performed. Here, 8/404 (1.98 %) patients showed contra- or bilateral bleeding. Only in 2/251 (0.7 %) patients occurred a bleeding complication after unilateral ABTE. Therefore, bleeding after unilateral ABTE was significantly lower than ABTE with contralateral TE (1.98 % vs. 0.7 %, p= 0.001). In 0.8 % of the patients a contralateral ABTE was necessary due to a metachronous PTA. Conclusion Overall, the rate of postoperative bleeding after ABTE (1.5 %) was low. Unilateral ABTE showed significantly lower postoperative bleeding rates compared to ABTE with contralateral TE. Consequently, the indication of a contralateral TE must be very strict.
CRIS-Team WoS Importer:2022-06-03